Manejo agro-técnico del cultivo de mora de castilla (Rubus glaucus), en la sierra ecuatoriana - Zumba Briones, Joyce Anahí (2022)
Agro-technical management of Castilla blackberry (Rubus glaucus) crop in the Ecuadorian highlands. The present research work was carried out to acquire and improve knowledge about the agro-technical management of the Castile blackberry (Rubus glaucus) crop in the Ecuadorian highlands. Blackberry cultivation in the Ecuadorian highlands is well accepted and generates good profitability knowing how to carry out production correctly, small and medium-sized producers live from this crop in most of the Ecuadorian highlands, because the highlands consist of an excellent climate for the production of this crop, are favorable for the good development of the fruit, which is the main demand in the market. This cultivar is most developed in the Sierra region, specifically in the provinces of Tungurahua and Bolívar, where most of the annual production is concentrated. To plan the production of the blackberry crop, soil conditions, fertility, pest and disease history must be identified, as well as other important variables such as planting, labor availability, fertilization, sustainable cultural practices, irrigation, etc. pruning. It is also important that the appropriate agricultural tasks are carried out, such as: irrigation, weed control, fertilization, pest and disease control, and adequate harvesting, in order to obtain better and higher productivity.